Efficient, Hysteresis‐Free, and Flexible Inverted Perovskite Solar Cells Using All‐Vacuum Processing. Issue 1 (9th November 2020) - Tavakoli, Mohammad Mahdi; Yadav, Pankaj; Prochowicz, Daniel; Tavakoli, Rouhollah
Abstract : The fabrication of efficient perovskite solar cells (PSCs) using all‐vacuum processing is still challenging due to the limitations in the vacuum deposition of the hole transporting layer (HTL). Herein, inverted PSCs using copper (II) phthalocyanine (CuPC) as an ideal alternative HTL for vacuum processing are fabricated. After proper optimization, a PSC with a power conversion efficiency (PCE) of 20.3% is achieved, which is much better than the PCEs (16.8%) of devices with solution‐based CuPC. As it takes a long time to dissolve CuPC in the solution‐based device, the evaporation approach has better advantage in terms of fast processing. In addition, the device with the evaporated CuPC HTL indicates an excellent operational stability, showing only 9% PCE loss under continuous illumination after 100 h, better than its counterpart device. Interestingly, the device shows negligible hysteresis. As all fabrication processes are conducted at low temperatures, flexible PSCs are also fabricated on ITO/PET substrates and a PCE of 18.68% is obtained. After 200 bending cycles, the flexible device retains 87.5% of its initial PCE value, indicating its great flexibility. Herein, the role of a suitable HTL for the fabrication of all‐vacuum‐processing PSCs with great efficiency and stability is highlighted. Abstract : Herein, all‐vacuum‐processed perovskite solar cells are reported in an inverted device architecture using copper (II) phthalocyanine (CuPC) as the hole transporting layer (HTL), and power conversion efficiencies (PCEs) of 20.3% and 18.68% on rigid and flexible substrates are achieved, respectively.